2002
DOI: 10.1269/jrr.43.s137
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Frequency of Plasmid DNA and Escherichia coli Following Long-term Space Flight on Mir

Abstract: To elucidate the biological influence of space radiation, we studied the effects of long-term space flight on mutation of the bacterial ribosomal protein L gene (rpsL). We prepared dried samples of plasmid DNA and repair-deficient and wild type cells of Escherichia (E.) coli. After a 40-day space flight on board the Russian space station Mir, the mutation frequencies of the rpsL gene were estimated by transformation of E. coli and by assessment of conversion of rpsL wild type phenotype (SmS) to its mutant phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…S2 in the supplemental material), suggesting that life aboard the space station was not accompanied by an accumulation of mutations presumably from enhanced exposure to irradiation and microgravity; however, since the proper terrestrial control strains do not exist for ISSFT-021 and IF1SW-F4, we cannot determine/quantify mutations that may have accumulated during time aboard the ISS. Interestingly, previous data suggest that DNA damage resulting from time aboard the ISS may favor chromosomal aberrations and large deletions over point mutations (2830), a conclusion that may have been fueled by studies that reported finding no detectable mutations from time in space, although these experiments utilized experimental setups that would favor detection of point mutations over large genetic lesions, or the studies were possibly too short in duration for mutations to accumulate (44). Sequence analysis with ISS A. fumigatus strains suggested that there is no enrichment for any type of mutation we could identify through our resequencing-based mapping approach, namely, indels, in comparison with Af293 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S2 in the supplemental material), suggesting that life aboard the space station was not accompanied by an accumulation of mutations presumably from enhanced exposure to irradiation and microgravity; however, since the proper terrestrial control strains do not exist for ISSFT-021 and IF1SW-F4, we cannot determine/quantify mutations that may have accumulated during time aboard the ISS. Interestingly, previous data suggest that DNA damage resulting from time aboard the ISS may favor chromosomal aberrations and large deletions over point mutations (2830), a conclusion that may have been fueled by studies that reported finding no detectable mutations from time in space, although these experiments utilized experimental setups that would favor detection of point mutations over large genetic lesions, or the studies were possibly too short in duration for mutations to accumulate (44). Sequence analysis with ISS A. fumigatus strains suggested that there is no enrichment for any type of mutation we could identify through our resequencing-based mapping approach, namely, indels, in comparison with Af293 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…of astronauts during long-term space flights, risk assessment and management, and cancer treatment strategies (Delone et al, 1991;Wang and Cai, 2000;Upton, 2001;Takahashi et al, 2002;Bonner, 2003;Mortazavi et al, 2003aMortazavi et al, , 2003bLiu, 2003;Schaffer et al, 2004;Preston, 2005). In preliminary cytogenetic studies, after in vitro irradiation with a test dose of gamma rays, a strong cytogenetic AR was induced in the lymphocytes of residents of the very high background radiation areas of Ramsar (Ghiassi-nejad et al, 2002).…”
Section: Relevance Of the Adaptive Responsementioning
confidence: 99%
“…For some microorganisms, growth and viability were measured during space missions. A 14-days exposure of Escherichia coli on the Space Shuttle or 140-d exposure on Mir did not result in any differences in viability and mutations frequencies in comparison to ground controls [154,155]-the same was the case in Saccharomyces cerevisiae [156]. Using repair-deficient E. coli mutants, DNA polymerase, and 3′→5′ exonuclease were identified as the most important enzymes for GCR-induced DNA damage in E. coli [157].…”
Section: Cellular Survival Cell Death and Proliferationmentioning
confidence: 71%